Translating China's Ambitions in the Energy Sector: Sinopec's Internationalization Strategy and Deepening Cooperation with Angola - Rivai, Aspin Nur Arifin; Pababbari, Musafir; Saleh, Eliza Farahdiba (Prodi Hubungan Internasional Program Magister Univ. Muhammadiyah Yogyakarta, 2025)
The internationalization of Chinese state-owned enterprises (SOEs) has emerged as a prominent phenomenon in global trade and political dynamics. Sinopec, one of China's leading SOEs in the energy sector, exemplifies this trend through its engagement in Angola. This research explores Sinopec’s internationalization strategies, focusing on its motivations, the geopolitical context of its operations, and its contributions to both China’s energy security and Angola’s economic recovery. Utilizing a qualitative methodology, this study analyzes secondary data from government reports, academic sources, and policy documents. Findings reveal that Sinopec’s expansion is driven by China's long-term goals of energy security and geopolitical influence, aligning with broader initiatives such as the Belt and Road Initiative (BRI). Moreover, Sinopec’s investments have significantly contributed to Angola’s infrastructure development, although concerns persist about environmental impact, governance, and local social dynamics.